2014
DOI: 10.1615/critrevoncog.2014011987
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Raf Kinase Inhibitor Protein (RKIP) in Multiple Cancer Types

Abstract: Raf kinase inhibitor protein (RKIP), an inhibitor of several signaling pathways, has been shown to have metastasis suppressor gene activity and promote apoptosis. While first identified in prostate cancer, RKIP's anti-metastasis properties have now been demonstrated in multiple tumor types. Furthermore, loss of RKIP expression is observed in many cancers as they progress. In this review, we provide a survey of the many tumor types in which RKIP function or expression has been evaluated. Particular attention is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 0 publications
4
49
0
1
Order By: Relevance
“…On the other hand, our results showed a statistical correlation with the absence of RKIP molecule expression and poor prognosis of STSs (table 2). These data are in accordance with other papers from our group, evaluating the RKIP protein expression profile in different types of tumors such as gastrointestinal stromal tumors, bladder cancer, gastric cancer and gliomas [12,15,21,22,23,24,25,30]. Thus, in the present study we showed that RKIP immunohistochemistry loss is an independent prognostic factor in a well-characterized series of 87 STSs [16,17,18].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, our results showed a statistical correlation with the absence of RKIP molecule expression and poor prognosis of STSs (table 2). These data are in accordance with other papers from our group, evaluating the RKIP protein expression profile in different types of tumors such as gastrointestinal stromal tumors, bladder cancer, gastric cancer and gliomas [12,15,21,22,23,24,25,30]. Thus, in the present study we showed that RKIP immunohistochemistry loss is an independent prognostic factor in a well-characterized series of 87 STSs [16,17,18].…”
Section: Discussionsupporting
confidence: 93%
“…Loss of RKIP expression is pathologically linked to cancer development [9,12,13,14,15], and initial studies have characterized it as a metastasis suppressor [14]. RKIP is a bona fide inhibitor of RAF-MEK-1 by preventing activation of the RAF/MEK/ERK signal transduction [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Octreotide may reduce the probability of invasion and metastasis in SKHep-1 cells by upregulating PEBP1. PEBP1 has been widely studied as a suppressor of tumor metastasis in many types of tumors [15]. Similarly, we observed lower expression of PEBP1 in highly invasive liver cancer cell line SK-Hep-1 and MHCC-97H as compared to minimally invasive cell line HepG2 and Huh7 (Fig.…”
Section: Octreotide Upregulates Pebp1supporting
confidence: 72%
“…RKIP can inhibit the activity of MAPK signaling through interaction with Raf-1, and is also involved in regulating PKC, G-protein-coupled receptors, and the NF-κB pathway [21]. Because PEBP1 can inhibit tumor metastasis, it is also considered a tumor suppressor gene [15].…”
Section: Discussionmentioning
confidence: 99%